Factors Influencing the Occurrence of Neonatal Asphyxia at Palembang Bari General Hospital - Rehana; Nurul Komariah; Khotimah (CV. AFDIFAL MAJU BERKAH, 2025)
Background: Asphyxia Neonatorum is one of the highest causes of infant mortality, which is 31.1%. Many factors cause Asphyxia Neonatorum of maternal factors (hypoxia in the mother, maternal age, gravida more than 4, hypertension, and congenital diseases), placental factors (placental abruption, placenta previa), fetal factors (premature, gemelli, LBW, congenital amniotic fluid mixed with meconium, abnormalities of the umbilical cord), and . factors of labor (long labor or parturition with action). Research Objectives: To find out the factors that influence the occurrence of Asphyxia Neonatorum at Palembang BARI Hospital in 2023. Research Methods: This type of research is a case-control study. The population is all newborns registered in the perinatology room register at Palembang Bari Hospital in 2021 and 2022, namely 1195 newborns, with the number of newborns experiencing Asphyxia Neonatorum as many as 72 cases. A sample of 144 newborns consisted of 72 respondents for the case group and 72 respondents for the control group. Data were analyzed univariate and bivariate using the chi-square test. Results: The results of statistical analysis showed a p-value <0.05 so there was a relationship between maternal age (p value=0.004), placenta previa (p value=0.025), premature rupture of membranes (p value=0.016), prolonged labor events (p-value = 0.015) with Asphyxia Neonatorum. Conclusion: there is a relationship between factors (maternal age, placenta previa, premature rupture of membranes, prolonged labor) with the incidence of Asphyxia Neonatorum at Palembang Bari Hospital in 2023. Suggestion : It is hoped that this research can add to knowledge and insight so that it becomes one of the efforts in preventing asphyxia neonatorum at Palembang Bari’s Hospital